2012
DOI: 10.1016/j.geomphys.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Universal curvature identities II

Abstract: Abstract. We show that any universal curvature identity which holds in the Riemannian setting extends naturally to the pseudo-Riemannian setting. Thus the Euh-Park-Sekigawa identity also holds for pseudo-Riemannian manifolds. We study the Euler-Lagrange equations associated to the Chern-Gauss-Bonnet formula and show that as in the Riemannian setting, they are given solely in terms of curvature (and not in terms of covariant derivatives of curvature) even in the pseudo-Riemannian setting. MSC 2010: 53B20.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…We demonstrated that the obtained curvature identity holds on any 4-dimensional Riemannian manifold which is not necessarily compact [11]. Further, Gilkey, Park and Sekigawa extended the result to the higher dimensional setting, the pseudo-Riemannian setting, manifolds with boundary setting and the Kähler setting [13,14,15,16]. In this paper, we shall give a curvature identity explicitly which holds on any 6-dimensional Riemannian manifold using methods similar to those used in the 4-dimensional Chern-Gauss-Bonnet theorem and also provide some applications of the obtained curvature identity.…”
Section: Introductionmentioning
confidence: 73%
“…We demonstrated that the obtained curvature identity holds on any 4-dimensional Riemannian manifold which is not necessarily compact [11]. Further, Gilkey, Park and Sekigawa extended the result to the higher dimensional setting, the pseudo-Riemannian setting, manifolds with boundary setting and the Kähler setting [13,14,15,16]. In this paper, we shall give a curvature identity explicitly which holds on any 6-dimensional Riemannian manifold using methods similar to those used in the 4-dimensional Chern-Gauss-Bonnet theorem and also provide some applications of the obtained curvature identity.…”
Section: Introductionmentioning
confidence: 73%
“…If P n,C is a universal scalar curvature identity in the curvature tensor in signature (p, q), then P n,C is a universal scalar curvature in any other signature (p,q) if p + q =p +q. In the discussion of [17], we first passed to the algebraic setting and then used analytic continuation. The reason to avoid dealing with the covariant derivatives of the curvature tensor was the relation…”
Section: Spaces Of Invariantsmentioning
confidence: 99%
“…Furthermore, it is now clear that the restriction of a universal curvature identity in dimension m generates a corresponding universal curvature identity in dimension m − 1. One has [13,15,17]: Theorem 2.3. Adopt the notation established above.…”
Section: Spaces Of Invariantsmentioning
confidence: 99%
“…This involves, of course, examining the associated Euler-Lagrange equations for this functional. Indefinite signatures are also important; Gilkey, Park and Sekigawa examined the Euler-Lagrange equations in the higher signature setting [10].…”
Section: Introductionmentioning
confidence: 99%